Diagnostic agreement of conventional and inverted scanned panoramic radiographs in the detection of the mandibular canal and the mental foramen. - Sakakura, Celso Eduardo; Loffredo, Leonor de Castro Monteiro; Scaf, Gulnara (American Academy of Implant Dentistry, 2004)
The aim of this study was to evaluate the diagnostic agreement of conventional panoramic radiographs and their inverted scanned images in the detection of the mandibular canal and mental foramen. A total of 77 panoramic radiographs obtained from the files of totally edentulous patients were used. Digitization was done by means of a scanner with brightness and contrast adjustment, as well as image inversion. The extension of mandibular canal was divided into anterior, middle, and posterior regions, and the presence of a radiopaque line that characterized the mandibular canal was classified according to a 5-point confidence scale. The mental foramen was classified in 4 types: continuous, separated, diffuse, and unidentified. Both conventional and inverted scanned panoramic radiographs were evaluated by 3 calibrated implantologists at 2 distinct moments with a minimum interval of 10 days between them. Intraexaminer agreement was evaluated by Kappa statistics by point and by 95% confidence interval. Because the intraexaminer level of agreement was low, interexaminer agreements could not be carried out. The results showed a substantial (in 2 situations), moderate (in 16 situations), and fair (in 18 situations) intraexaminer agreement for mandibular canal and a substantial (in 1 situation), fair (in 1 situation), and moderate (in 10 situations) intraeaminer agreement for mental foramen. There were no statistically significant differences in most instances. In conclusion, the diagnostic agreement of conventional and inverted scanned panoramic radiographs for detection of mandibular canal and mental foramen was low.
Keywords: calibration; confidence interval; histology; human; image processing; image quality; mandible; methodology; molar tooth; mouth disease; observer variation; panoramic radiography; premolar tooth; radiography; reproducibility; statistics; tooth root; Bicuspid; Calibration; Confidence Intervals; Humans; Image Processing, Computer-Assisted; Mandible; Molar; Molar, Third; Mouth, Edentulous; Observer Variation; Radiographic Image Enhancement; Radiography, Panoramic; Reproducibility of Results; Tooth Apex